Dose optimization of vancomycin in obese patients: A systematic review - Elrggal, Mahmoud E.; Haseeb, Abdul; AlGethamy, Manal; Ahsan, Umar; Saleem, Zikria; Althaqafi, Areej Sultan; Alshuail, Sattam Saad; Alsiddiqi, Zohair Ahmad; Iqbal, Muhammad Shahid; Alzahrani, Albaraa Faraj; AlQarni, Abdullmoin; Radwan, Rozan Mohammad; et al. (Frontiers in Pharmacology, 2023)
Background: Dose optimization of vancomycin plays a substantial role in drug pharmacokinetics because of the increased incidence of obesity worldwide. This systematic review was aimed to highlight the current dosing strategy of vancomycin among obese patients. Methods: This systematic review was in concordance with Preferred Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. The literature search was carried out on various databases such as Scopus, PubMed/MEDLINE, ScienceDirect and EMBASE using Keywords and MeSH terms related to vancomycin dosing among obese patients. Google Scholar was also searched for additional articles. The English language articles published after January, 2000 were included in this study. The quality of the study was assessed using different assessment tools for cohort, and case reports. Results: A total of 1,029 records were identified. After screening, 18 studies were included for the final review. Of total, twelve studies are retrospective and remaining six are case-control studies. A total of eight studies were conducted in pediatrics while remaining studies were conducted in adult population. Most of the studies reported the dosing interval every 6–8 h. Differences in target trough concentration exist with respect to target ranges. The administration of loading dose (20–25 mg/kg) followed by maintenance dose (15–25 mg/kg) of vancomycin is recommended in adult patients to target therapeutic outcomes. Moreover, a dose of 40–60 mg/kg/day appears appropriate for pediatric patients. Conclusion: The initial dosing of vancomycin based on TBW could be better predictor of vancomycin trough concentration. However, the clinical significance is uncertain. Therefore, more studies are needed to evaluate the dosing strategy of vancomycin in overweight or obese patients.